Simulation of Intermetallic Synthesis in a Cylindrical Mold under Induction Heating; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Bukrina N. V. (2018, 2018)
Title screen